The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1016/j.ijscr.2020.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Dual mobility acetabular construct with freedom constrained liner for treatment of recurrent dislocations after total hip arthroplasty: A case report and literature review

Abstract: Highlights Dual-mobility bearings improve stability in total hip arthroplasty (THA) but may fail to prevent postoperative dislocation. Dry revision with a compatible constrained liner system can provide an effective salvage option for instability after THA. The unique G7 constrained liner system offers good short-term stability and range of motion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…According to Gaillard et al [ 7 ], dual mobility articular surfaces are better than traditional bearing surfaces as they provide good stability and a high survival rate in both primary and revision surgeries. Onochi et al [ 8 ] in their study used freedom constrained liner for recurrent dislocation, in a schizophrenic patient who underwent dual mobility total hip arthroplasty already and concluded that freedom liner may provide salvage solution for joint instability in dual mobility total hip arthroplasty as in our case till the time no history of dislocation. Gianluca et al [ 9 ] found that dual mobility total hip arthroplasty in femur neck fracture has good clinical outcome and low rate of dislocation.…”
Section: Discussionmentioning
confidence: 59%
“…According to Gaillard et al [ 7 ], dual mobility articular surfaces are better than traditional bearing surfaces as they provide good stability and a high survival rate in both primary and revision surgeries. Onochi et al [ 8 ] in their study used freedom constrained liner for recurrent dislocation, in a schizophrenic patient who underwent dual mobility total hip arthroplasty already and concluded that freedom liner may provide salvage solution for joint instability in dual mobility total hip arthroplasty as in our case till the time no history of dislocation. Gianluca et al [ 9 ] found that dual mobility total hip arthroplasty in femur neck fracture has good clinical outcome and low rate of dislocation.…”
Section: Discussionmentioning
confidence: 59%
“…Dual mobility cup (DMC) comprises a small head connected to a polyethylene liner. The aim of DMC is to enhance ROM and better stabilization [41]. It provides a lesser risk of dislocation in cases more prone to that complication-especially in case of neurological diseases, accompanied by increased or decreased muscle tonicity, e.g., multiple sclerosis, or bone defects [41].…”
Section: Discussionmentioning
confidence: 99%
“…(a) Prosthetic loosening of the implant; (b) dislocation of the implant. Adapted with permission from ref . Copyright 2023, Elsevier.…”
Section: Hip Implant Failuresmentioning
confidence: 99%
“…The basic mechanical properties of ceramics are illustrated in Table . Although ceramics provide several supporting properties, less than 10% of hip procedures are performed exclusively due to their complexity, high cost, risk of catastrophic failure, and lack of familiarity . Alumina and zirconia, which are discussed below in depth, are widely used ceramic materials for hip arthroplasty.…”
Section: Ceramic-based Hip Implantsmentioning
confidence: 99%